Preparation method of oil-soluble NiOx nano-particles as well as product and application of oil-soluble NiOx nano-particles

By preparing oil-soluble NiOx nanoparticles, the problem of NiOx nanomaterials not being able to spin-coat on the perovskite layer is solved, and its effective application in perovskite solar cells is achieved, providing higher hole mobility and better stability.

CN119683699APending Publication Date: 2025-03-25XIAN POLYMER LIGHT TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411839038.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

In the prior art, NiOx nanomaterials cannot be spin-coated on the perovskite layer because water in the aqueous dispersion will destroy the perovskite coating and cause the perovskite to dissociate.

Method used

Using the preparation method of oil-soluble NiOx nanoparticles, a highly conductive oil-soluble NiOx nanoparticles are obtained by mixing nickel salts, organometallic salts with surfactants and heating them under high temperature conditions to form a precursor solution of nickel, and then adding organic alcohols and ethanol. After multiple centrifugation precipitation and dispersion of oily solvents, highly conductive oil-soluble NiOx nanoparticles are obtained.

Benefits of technology

The oil solubility of NiOx nanoparticles is achieved, so that they can be dissolved in organic solvents such as alkanes. As the hole transport layer material of the regular device, it avoids damage to the perovskite coating, and its hole mobility, ultraviolet light resistance, thermal stability and weather resistance are all better than the traditional sprio-OMeTAD materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119683699A_ABST
    Figure CN119683699A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of solar cells, and particularly relates to a preparation method of oil-soluble NiOx nanoparticles, a product of the oil-soluble NiOx nanoparticles and application of the oil-soluble NiOx nanoparticles. According to the method, the oil-soluble NiOx nanoparticles are obtained through a high-temperature thermal decomposition method and can be dissolved in organic solvents such as alkane to serve as organic solvents which can be suitable for being used in an upright device structure; the nanoparticles comprise a NiOx inorganic matter and an organic ligand on the surface of the NiOx inorganic matter, and the conductive ink comprises oil-soluble NiOx, a stabilizer, a first solvent, a second solvent, a defoaming agent and a flatting agent. The conductive ink has high stability and can be stored at room temperature for a long time. According to the invention, the problem that conventional nickel oxide cannot be spin-coated on a perovskite layer is solved, and expensive sprio-OMeTAD is replaced by oil-soluble NiOx nanoparticles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solar cells, and particularly relates to an oil-soluble NiO x Nanoparticle preparation method, products and applications. Background Art

[0002] With the development of science and technology, perovskite solar cells are becoming well-known as a new technology. The hole transport layer material used in the device is mainly sprio-OMeTAD, but due to its high price, the device life is short. NiOx nanomaterials are widely used in the field of perovskite solar cells because they have a suitable energy level match with perovskite, a high hole mobility, and are easy to synthesize and low in cost.

[0003] Conventional NiOx is usually prepared as an aqueous dispersion and then spin-coated on ITO and FTO transparent electrodes, but it cannot be used on upright devices because in upright devices, the hole transport layer material is spin-coated on the perovskite coating, and the water in the NiOx aqueous dispersion will destroy the perovskite coating, causing the perovskite to dissociate. Summary of the invention

[0004] In view of the above technical problems, the present application provides an oil-soluble NiO x The preparation method of nanoparticles, its products and applications are used to solve the problem that conventional NiOx cannot be spin-coated on the perovskite layer, replacing the more expensive sprio-OMeTAD.

[0005] The technical solution adopted by the present invention is as follows:

[0006] Oil-soluble NiO x The method for preparing nanoparticles comprises the following steps:

[0007] S1. Mixing nickel salt, organic metal salt, surfactant and organic solvent, dissolving transparently under vacuum and heating at 50-120°C to form a first reaction system, a nickel precursor solution;

[0008] S2. Under high temperature conditions, a linear or branched organic alcohol having a carbon chain number of 2-20 is added to the first reaction system to obtain a second reaction system, and the mixture is kept warm for 0.2-24h to form nanoparticles;

[0009] S3. Adding excess ethanol to the product of the second reaction system, centrifuging and precipitating several times, and dispersing with an oily solvent to obtain a nanoparticle dispersion, ie, a third reaction system;

[0010] S4. One or more of a straight-chain or branched carboxylic acid having 2 to 20 carbon atoms and a straight-chain or branched thiol having 2 to 20 carbon atoms are mixed evenly with the third system in a molar ratio of (0.1 to 10):1, and then ultrasonically treated for 0.1 to 24 hours to obtain a highly conductive oil-soluble NiO x Nano-solution mixture;

[0011] S5. The mixture is then precipitated and centrifuged with a poor solvent and purified multiple times. The resulting precipitate is oil-soluble nanoparticles, which are then dissolved in an oily alkane solvent.

[0012] Furthermore, in step S1, the overall feed ratio of nickel salt to organic metal salt is 1:(0.5-3) based on the amount of substance.

[0013] Furthermore, the high temperature condition in S2 refers to 120°C-350°C.

[0014] The oil-soluble NiO prepared by any of the above preparation methods x Nanoparticles comprising NiO x Inorganic substances and NiO x Organic ligands on the surface of inorganic substances.

[0015] Furthermore, the organic ligand is one or more of a straight-chain or branched carboxylic acid having 2-20 carbon atoms, and a straight-chain or branched thiol having 2-20 carbon atoms.

[0016] Furthermore, the particle size of the nanoparticles is 3-10 nm.

[0017] Furthermore, the weight of the organic ligand accounts for 3%-30% of the whole.

[0018] As mentioned above, oil-soluble NiO x Application of nanoparticles as materials for perovskite solar cells.

[0019] A conductive ink comprising the oil-soluble NiO x , stabilizer, first solvent, second solvent, defoamer and leveling agent.

[0020] Furthermore, the stabilizer is an organic substance having the ability to coordinate with Ni, the first solvent is one or more linear or aromatic alkanes with a carbon chain number of 8-13, the second solvent is a film surface modifier, the defoamer is a low-viscosity polydimethylsiloxane, and the leveling agent is a fluorinated ester with a carbon chain number between 9 and 18.

[0021] The beneficial effects of the present invention are as follows:

[0022] The present invention obtains oil-soluble oxide nanoparticles by high-temperature thermal decomposition, which can be dissolved in organic solvents such as alkanes and used as hole transport layer materials for orthogonal device structures. Based on alkanes and perovskite solvents (DMF and DMSO are orthogonal solvents), alkanes will not destroy the perovskite coating, and their hole mobility is higher than that of sprio-OMeTAD, and the hole mobility of sprio-OMeTAD is 1.0x10^-4cm 2 V -1 s -1 , while NiO x 0.1-3.0cm 2 V -1 s -1 . Plus NiO x The UV resistance, thermal stability and weather resistance of this application are stronger than those of sprio-OMeTAD. x Nanomaterials can serve as alternatives to sprio-OMeTAD.

[0023] The present invention utilizes the strong coordination ability of thiol and carboxyl groups with nickel to stabilize NiO in alkane oily ink for a long time. x Nanoparticles; in addition, alcohols, pinene alcohol, and polydimethylsiloxane can provide suitable viscosity, leveling, and volatility, and the obtained quantum dot conductive ink meets the requirements of spin coating, printing, and spraying. The obtained conductive ink has high stability and can be stored for a long time at room temperature. It will not agglomerate, precipitate, or delaminate within one year. When spin coating, a uniform NiOx film can be obtained; when printing, the nozzle will not be blocked, and the coffee ring effect can be suppressed. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 NiO prepared by the present invention x TEM image of nanoparticles.

[0025] Figure 2 NiO prepared by the present invention x XRD pattern of nanoparticles.

[0026] Figure 3 NiO prepared by the present invention x UV-visible absorption graph of nanoparticles.

[0027] Figure 4 NiO prepared by the present invention x Thermogravimetric analysis of nanoparticles. DETAILED DESCRIPTION

[0028] The present invention is described in detail below through specific embodiments.

[0029] The present invention provides a method for preparing oily NiOx nanoparticles, comprising the following steps:

[0030] S1. Mixing nickel salt, organic metal salt, surfactant and organic solvent, dissolving transparently under vacuum and heating at 50-120°C to form a first reaction system, a nickel precursor solution;

[0031] S2. Under high temperature conditions, a linear or branched organic alcohol having a carbon chain number of 2-20 is added to the first reaction system to obtain a second reaction system, and the mixture is kept warm for 0.2-24h to form nanoparticles;

[0032] S3. Adding excess ethanol to the product of the second reaction system, centrifuging and precipitating several times, and dispersing with an oily solvent to obtain a nanoparticle dispersion, namely, the third reaction system;

[0033] S4. The ligand modifier and the third system are mixed evenly according to a molar ratio of 0.1-10:1, and then ultrasonically treated for 0.1-24h to obtain a highly conductive oil-soluble NiOx nano-solution mixture;

[0034] S5. The mixture is then precipitated and centrifuged with a poor solvent and purified multiple times. The resulting precipitate is oil-soluble nanoparticles, which are then dissolved in an oily alkane solvent.

[0035] The oil solubility in the present application refers to the property of being able to be dissolved or dispersed in straight-chain or branched alkanes with a carbon chain number of 5-20.

[0036] The nickel salt in S1 can be selected from but not limited to nickel nitrate and its hydrate, nickel chloride and its hydrate, nickel acetate and its hydrate, nickel sulfate and its hydrate, nickel bromide and its hydrate, nickel acetylacetonate and its hydrate, nickel dibutyldithiocarbamate, nickel diethyldithiocarbamate, nickel oxalate, nickel phosphate, nickel xanthate, nickel ethylenediaminetetraacetic acid, nickel isopropoxide, nickel 8-hydroxyquinoline, nickel stearate, nickel oleate, nickel hypophosphite and its hydrate, nickel fluoride, basic nickel carbonate, nickel perchlorate, nickel benzoate, nickel thiocyanate, and nickel trifluoromethanesulfonate.

[0037] The organic metal salt in S1 can be selected from but not limited to one or more of alkali metal oleate and alkali metal stearate. The surfactant can be selected from but not limited to one or more of unsaturated or saturated straight chain or branched chain carboxylic acids with 6-20 carbon atoms, preferably oleic acid and stearic acid.

[0038] In terms of the amount of substance, the overall feed ratio of the nickel salt and the organic metal salt is 1:(0.5-3);

[0039] The high temperature condition in S2 refers to 120°C-350°C, which is mainly to provide activation energy for the NiOx nucleation reaction. If the temperature is too low, it is not conducive to the reaction; if the temperature is too high, the particle size of the nanoparticles is not uniform. Preferably, it is 260°C-300°C.

[0040] The addition of straight-chain or branched organic alcohols in S2 is mainly to provide active hydroxyl groups for reaction with nickel precursors. Organic acid nickel will react with alcohols to generate organic esters at high temperatures, and NiOx is only a byproduct. Since this reaction is irreversible, the reaction of generating nanoparticles continues. The insulation time is mainly for the generation reaction of nanomaterials. During this process, the particle size of the nanomaterials will gradually increase over time.

[0041] S3 is to remove impurities in the nanoparticles to facilitate the next step of ligand exchange.

[0042] The ligand modifier in S4 refers to a straight-chain or branched carboxylic acid with 2-20 carbon atoms or a straight-chain or branched thiol with 2-20 carbon atoms. The purpose is to control the growth of nanoparticles and secondly to convert NiO x The long chains on the surface are replaced by short chains, which significantly improves the electrical conductivity of the nanomaterial. The third is to shorten the distance between particles in the nanoparticle coating.

[0043] S5 is to purify the nanomaterials and redissolve them in an alkane oily solvent to form a spin coating solution.

[0044] The nanomaterial is divided into NiO x It consists of two parts: inorganic components and organic ligands.

[0045] The particle size of nanoparticles is 3-10nm.

[0046] The surface of the nanoparticles carries some organic ligands, which are composed of the following organic substances: straight-chain or branched carboxylic acids with 2-20 carbon atoms, straight-chain or branched thiols with 2-20 carbon atoms;

[0047] The weight of the ligands on the surface of the nanomaterial accounts for 3% to 30% of the total weight, preferably between 10% and 15%.

[0048] The present invention also provides a NiO x Nanoparticles prepared according to the above method. NiO x Nanoparticles include NiO x Inorganic, NiO x The organic ligand composition on the surface. The band gap is calculated to be in the range of 3.6 eV-4.0 eV. The calculation method is well known to those skilled in the art, for example, it can be calculated by the Tauc Plot method, and will not be described in detail here.

[0049] The hole mobility of the nanomaterials of the present invention is 0.1-5.0 cm 2 V -1 s -1 between.

[0050] The nano-oily nano-material of the present invention is mainly used as a hole transport material in an orthogonal perovskite solar cell. Specifically, the nano-material can be deposited on a perovskite light absorbing layer material by spin coating, spray coating, inkjet printing, etc.

[0051] According to another aspect of the present invention, there is provided an oily NiO x Conductive inks, including oily NiO x And a stabilizer and a first solvent, a second solvent. The stabilizer is an organic substance that coordinates with Ni, such as a straight-chain or branched carboxylic acid with a carbon number of 2-20, a straight-chain or branched thiol with a carbon number of 2-20, and the main purpose is to stabilize NiOx to prevent it from falling off or being reduced to divalent nickel and conductive ink; the first solvent is one or more straight-chain or aromatic alkanes with a carbon chain number of 8-13, which mainly serve as the main solvent; such as n-octane, n-nonane, toluene, and xylene; the second solvent is a film surface modifier, such as pine alcohol and linalool; a defoamer, a low-viscosity polydimethylsiloxane. Leveling agent, a fluorinated ester with a carbon chain number between 9 and 18, such as methyl perfluorooctanoate, such as ethyl perfluorododecanoate, methyl perfluorododecanoate. These mainly function to reduce the contact angle, increase the wettability of the membrane surface, level it, eliminate foam, and inhibit the coffee ring effect.

[0052] The mercaptan, such as ethyl mercaptan, propyl mercaptan, butyl mercaptan, pentyl mercaptan, hexyl mercaptan, heptyl mercaptan, octyl mercaptan, nonyl mercaptan, decyl mercaptan, n-undecaptan, n-dodecyl mercaptan, etc., is preferably hexyl mercaptan.

[0053] The carboxylic acid includes but is not limited to n-butyric acid, n-pentanoic acid, n-hexanoic acid, etc., preferably n-hexanoic acid;

[0054] The first solvent includes but is not limited to n-octane, n-nonane, n-decane, n-undecane, n-dodecane, etc., preferably n-octane;

[0055] The polydimethylsiloxane includes but is not limited to polydimethylsiloxane having a viscosity of 100-10000 (mPa.s), preferably a viscosity of 300 mPa.s.

[0056] The leveling agent includes but is not limited to perfluoroesters with a carbon chain number of 6-22, such as methyl perfluorohexanoate, ethyl perfluorohexanoate, methyl perfluoroheptanoate, ethyl perfluoroheptanoate, etc.;

[0057] By controlling the content of different components, NiO can be tunedx Conductive ink viscosity, conductivity, contact angle, surface tension, film surface flatness, defoaming, etc., so that it can meet the requirements of inkjet printing, spin coating, and scraping coating for ink, and obtain a relatively good film. x In conductive ink, NiO x The content of is between 2% and 10%, the content of thiol compound is between 1% and 5%, the content of carboxylic acid is between 1% and 3%, the content of the first solvent is between 30% and 70%, and more preferably is 30%, 40%, 50%, 60%, and 70%; the content of film surface modifier is between 10% and 30%, and more preferably is 10%, 15%, 20%, 25%, and 30%; the content of polydimethylsiloxane is between 0.1% and 10%, and more preferably is 0.1%, 0.5%, 1%, 5%, and 10%; the content of fluorine-containing ester is between 0.1% and 5%, and more preferably is 0.1%, 0.5%, 1%, and 5%.

[0058] NiO x The conductivity of the conductive ink is 1-20μS / cm, which meets the needs of perovskite solar cells for hole transport materials.

[0059] A method for preparing oily NiO x The method of producing nanoparticles comprises the following steps:

[0060] Embodiment 1

[0061] S1. Mix 1mmol nickel nitrate, 1mmol sodium stearate, 10ml oleic acid and 15ml octadecene, and dissolve them transparently under vacuum and heating at 100°C to obtain a nickel oleate solution;

[0062] S2. The temperature of the above system was raised to 270°C, 2 mmol of n-dodecanol system and 1 ml of octadecene were heated at 100°C and added to the above high temperature system, and kept warm for 1 hour to form NiOx nanoparticles with a particle size of about 4 nm;

[0063] S3. Add 3 times the amount of ethanol to the above mother liquor, centrifuge and precipitate three times, dissolve with n-heptane to obtain n-heptane dispersed oily NiO x ;

[0064] S4. Oily NiO dispersed with n-hexanoic acid and n-heptane x Mix them evenly in a mass ratio of 1:10, and then ultrasonicate for 1 hour to obtain a NiOx nanoparticle solution exchanged with n-hexanoic acid;

[0065] S5. The mixture was purified by ethanol precipitation and centrifugation three times, and then dissolved in n-hexane.

[0066] Embodiment 2

[0067] S1. 1mmol nickel chloride, 1.5mmol lithium stearate, 17ml lauric acid and 15ml oleylamine were mixed and dissolved under vacuum and heated at 120°C to obtain a nickel laurate solution;

[0068] S2. The temperature of the above system was raised to 300°C, 2.5mmol of n-octadecyl alcohol and 2ml of oleylamine were added to the above high temperature system at 100°C and kept warm for 3h to form NiO x Nanoparticles, with a particle size of about 5nm;

[0069] S3. Add 3 times the amount of ethanol to the above mother liquor, centrifuge and precipitate three times, dissolve with n-heptane to obtain n-heptane dispersed oily NiO x ;

[0070] S4. Oily NiO dispersed in n-butyric acid and n-heptane x The mixture was mixed evenly in a mass ratio of 1:10, and then ultrasonically treated for 3 h to obtain NiO exchanged with hexanoic acid. x Nanoparticle solution;

[0071] S5. The mixture was purified by ethanol precipitation and centrifugation three times, and then dissolved in n-heptane.

[0072] Embodiment 3

[0073] S1. Mix 1mmol nickel sulfate, 2mmol sodium stearate and 2mmol stearic acid, and 15ml trioctylamine, and dissolve transparently under vacuum and heating at 120°C to obtain a nickel oleate solution;

[0074] S2. The temperature of the above system was raised to 310°C, 5 mmol of n-octadecyl alcohol and 1 ml of trioctylamine were added to the above high temperature system at 100°C, and kept warm for 3 hours to form NiO x Nanoparticles, with a particle size of about 5nm;

[0075] S3. Add 3 times the amount of ethanol to the above mother liquor, centrifuge and precipitate three times, dissolve with n-heptane to obtain n-heptane dispersed oily NiO x ;

[0076] S4. Dispersing oily NiO with octanethiol and n-heptane x The mixture was mixed evenly in a mass ratio of 1:5, and then ultrasonically treated for 0.5 h to obtain octanethiolate-exchanged NiO. x Nanoparticle solution;

[0077] S5. The mixture was then purified by ethanol precipitation and centrifugation three times, and then dissolved in n-octane.

[0078] Comparative Example 1

[0079] S1. At 25°C, 0.3 mol of nickel nitrate and 1 L of water were mixed to obtain a first reaction system;

[0080] S2. 0.6 mol of NaOH was added to the first reaction system, and the reaction was continued for 2 h to obtain a Ni(OH)2 sol dispersion system;

[0081] S3. The Ni(OH)2 sol dispersion is centrifuged and washed twice with water until the nitrate ions are completely eluted;

[0082] S4. S4 was calcined at 280℃ for 1h to obtain black NiO x calcined body;

[0083] S5. NiO x The nanopowder was ultrasonicated under an ultrasonic probe for 1 hour to obtain NiOx nano-aqueous dispersion.

[0084] Table 1: Comparison of device performance results in various embodiments

[0085]

[0086] Embodiment 4

[0087] This embodiment provides a NiO x Conductive ink, wherein NiOx is prepared according to Example 1 of the present application, and the formula is as follows: NiO x In conductive ink, NiO x The content of is 2.5%, the content of hexanethiol is 4%, the content of n-hexanoic acid is 2%, the content of n-octane is 40%, the content of n-decane is 20%, the content of n-dodecane is 10%; the content of turpentine is 20%; the content of polydimethylsiloxane with a viscosity of 300mPa.s is 1%; the content of methyl perfluorododecanoate is 0.5%.

[0088] Using the above NiO x Conductive ink can be used for inkjet printing for more than 1 hour, the ink conductivity is 10μS / cm, and the printing process is smooth, and a flat and uniform conductive film can be obtained.

[0089] Embodiment 5

[0090] This embodiment provides a NiO x Conductive ink, including NiO x It is prepared by Example 2 of the present application, and the formula is as follows: NiO x In conductive ink, NiO xThe content of is 3%, the content of octanol is 3.5%, the content of n-butyric acid is 2%, the content of n-octane is 35%, the content of isooctane is 25%, the content of n-dodecane is 10%; the content of turpentine is 20%; the content of polydimethylsiloxane with a viscosity of 300mPa.s is 1%; the content of ethyl perfluorohexanoate is 0.5%.

[0091] Using the above NiO x The ink can be used for inkjet printing and can be continuously printed for more than 1.5 hours. The ink conductivity is 10μS / cm, and the printing process is smooth, and a flat and uniform conductive film can be obtained.

[0092] The spin coating method comprises the following steps: spin coating an ethanol solution of zinc oxide on the IT0 anode layer, and then annealing at 80°C for 10 min to form an electron transport layer; spin coating a perovskite solution on the electron transport layer as a carrier to form an absorption layer; spin coating the NiO in Example 1 on the absorption layer x The nanomaterial n-octane dispersion forms a hole transport layer after drying; finally, a 100nm Au cathode electrode layer is evaporated and encapsulated to form a perovskite solar cell device.

[0093] Inkjet printing method: In the above spin coating method, only the spin coating process is changed to inkjet printing into the perovskite light absorbing layer material. Under high vacuum conditions, the NiOx layer material is annealed by a gradient temperature increase method, and then a 100nm Au cathode layer is evaporated.

[0094] The above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the scope of protection of the invention.

Claims

1. Oil-soluble NiO x A method for preparing nanoparticles, characterized in that: The following steps are involved: S1. Mixing nickel salt, organic metal salt, surfactant and organic solvent, dissolving transparently under vacuum and heating at 50-120°C to form a first reaction system, a nickel precursor solution; S2. Under high temperature conditions, a linear or branched organic alcohol having a carbon chain number of 2-20 is added to the first reaction system to obtain a second reaction system, and the mixture is kept warm for 0.2-24h to form nanoparticles; S3. Adding excess ethanol to the product of the second reaction system, centrifuging and precipitating several times, and dispersing with an oily solvent to obtain a nanoparticle dispersion, ie, a third reaction system; S4. One or more of a straight-chain or branched carboxylic acid having 2 to 20 carbon atoms and a straight-chain or branched thiol having 2 to 20 carbon atoms are mixed evenly with the third system in a molar ratio of (0.1 to 10):1, and then ultrasonically treated for 0.1 to 24 hours to obtain a highly conductive oil-soluble NiO x Nano-solution mixture; S5. The mixture is then precipitated and centrifuged with a poor solvent and purified multiple times. The resulting precipitate is oil-soluble nanoparticles, which are then dissolved in an oily alkane solvent.

2. The oil-soluble NiO according to claim 1 x The method for preparing nanoparticles is characterized by: In step S1, the overall feed ratio of nickel salt to organic metal salt is 1:(0.5-3) based on the amount of substances.

3. The oil-soluble NiO according to claim 1 x The method for preparing nanoparticles is characterized by: The high temperature condition in S2 refers to 120°C-350°C.

4. The oil-soluble NiO prepared by any one of the preparation methods of claims 1 to 3 x Nanoparticles comprising NiO x Inorganic substances and NiO x Organic ligands on the surface of inorganic substances.

5. The oil-soluble NiO according to claim 4 x Nanoparticles, characterized in that: The organic ligand is one or more of a straight-chain or branched carboxylic acid having 2-20 carbon atoms and a straight-chain or branched thiol having 2-20 carbon atoms.

6. The oil-soluble NiO according to claim 4 x Nanoparticles, characterized in that: The particle size of the nanoparticles is 3-10 nm.

7. The oil-soluble NiO according to claim 4 x Nanoparticles, characterized in that: The weight of the organic ligand accounts for 3%-30% of the whole.

8. The oil-soluble NiO according to claim 4 x Application of nanoparticles as materials for perovskite solar cells.

9. A conductive ink comprising the oil-soluble NiO as claimed in claim 4 x , stabilizer, first solvent, second solvent, defoamer and leveling agent.

10. The conductive ink according to claim 9, characterized in that: The stabilizer is an organic substance having the ability to coordinate with Ni, the first solvent is one or more linear or aromatic alkanes with a carbon chain number of 8-13, the second solvent is a membrane surface modifier, the defoamer is a low-viscosity polydimethylsiloxane, and the leveling agent is a fluorinated ester with a carbon chain number between 9 and 18.